(untitled) (Jurnal Manajemen Bisnis, 2026)
This study aimed to analyze the impact of profitability, capital adequacy, and liquidity on the stock prices of state-owned banking companies listed on the Indonesia Stock Exchange. A quantitative research design with a causal approach was employed, using secondary data from audited financial reports. The sample consisted of major state-owned banks selected through purposive sampling. Data analysis was performed using panel data regression with the Random Effects Model in EViews. Before the regression analysis, classical assumption tests were conducted to ensure the model met the requirements for normality, multicollinearity, heteroscedasticity, and autocorrelation. The results revealed that the Return on Assets and the Capital Adequacy Ratio did not have a significant effect on stock prices. In contrast, the Loan-to-Deposit Ratio was found to have a significant positive influence on stock valuations. The model demonstrated a meaningful adjusted R-squared value, indicating that the independent variables collectively explained a meaningful share of the variance in stock prices. These findings suggest that investors prioritize liquidity efficiency over internal profitability and capital metrics when valuing banking stocks in the Indonesian market. Consequently, banking management should maintain optimal liquidity levels to enhance market perception and drive investor confidence.